2016
DOI: 10.1186/s12867-016-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for protein palmitoylation and zDHHC16 in DNA damage response

Abstract: BackgroundCells respond to DNA damage by activating the phosphatidylinositol-3 kinase-related kinases, p53 and other pathways to promote cell cycle arrest, apoptosis, and/or DNA repair. Here we report that protein palmitoylation, a modification carried out by protein acyltransferases with zinc-finger and Asp-His-His-Cys domains (zDHHC), is required for proper DNA damage responses.ResultsInhibition of protein palmitoylation compromised DNA damage-induced activation of Atm, induction and activation of p53, cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…All the cancer patients and medical workers showed DNA damage but the extent of damage was significantly higher among the cancer patients. Similar findings have been reported by many earlier studies [21,[24][25][26] except one study in which the authors have reported negative results [27] . The comet tail length was surprisingly very low in both, treated (radiotherapy) and untreated cancer patients (ranging between 0.91 to 3.76).…”
Section: Discussionsupporting
confidence: 81%
“…All the cancer patients and medical workers showed DNA damage but the extent of damage was significantly higher among the cancer patients. Similar findings have been reported by many earlier studies [21,[24][25][26] except one study in which the authors have reported negative results [27] . The comet tail length was surprisingly very low in both, treated (radiotherapy) and untreated cancer patients (ranging between 0.91 to 3.76).…”
Section: Discussionsupporting
confidence: 81%
“…Its name Ablphilin stems from its ability to interact with the non-receptor tyrosine kinase c-Abl at the ER surface ( Li et al, 2002 ). ZDHHC16/Aph2 is essential for embryonic and postnatal survival, eye and heart development in mice ( Zhou et al, 2015 ), for the proliferation of neural stem cells, where it is involved in the activation of the FGF/erk pathways ( Shi et al, 2016 ) and was reported to play a role in DNA damage response ( Cao et al, 2016 ). Our findings raise the possibility that some of these effects may involve ZDHHC6.…”
Section: Discussionmentioning
confidence: 99%
“…However, the functional consequences for most targets of S- acylation remain to be determined. Interestingly, chemical inhibition of protein S -palmitoylation in mammalian cells led to a muted DNA-damage response 60 . Here, we uncover a role for protein S- acylation in DSB repair pathway choice.…”
Section: Discussionmentioning
confidence: 99%